The role of head and neck squamous cell carcinoma cancer stem cells in tumorigenesis, metastasis, and treatment failure - Chinn, Steven B.; Darr, Owen A.; Peters, R D.; Prince, Mark E. (Frontiers in Endocrinology, 2012)
Head and neck squamous cell cancer (HNSCC) is the 6th most common cancer worldwide. Despite advances in diagnostic and therapeutic methods, survival of HNSCC remains unchanged over the last 30 years with treatment failure and metastases being the strongest indicators of poor outcome. Cancer stem cells (CSC) have been identified in multiple other solid tumors, including breast, prostate and pancreatic carcinoma. Recently, a subpopulation of tumor cells has been identified in HNSCC based on the overexpression of the cellular marker CD44 and increased activity of aldehyde dehydrogenase. These cells have been designated CSC based on their stem cell-like properties: self-renewal, tumorigenesis and the ability to recapitulate a heterogeneous tumor. Recent work looking at the role of HNSCC CSC in tumorigenesis has shown that CSC have a greater capacity for tumor growth, increased motility and invasive characteristics; in-vivo experiments confirm greater metastatic potential in CSC compared to non-CSC. Clinically, CSC enrichment has been shown to be enhanced in recurrent disease, treatment failure and metastasis. Cancer stem cells represent a novel target of study given their slow growth and innate mechanisms conferring treatment resistance. Further understanding of their unique phenotype may reveal potential molecular targets to improve therapeutic and survival outcomes in patients with HNSCC.